Microbial community variations in adult Hyalomma dromedarii ticks from single locations in Saudi Arabia and Tunisia - Kratou, Myriam; Maitre, Apolline; Abuin-Denis, Lianet; Selmi, Rachid; Belkahia, Hanène; Alanazi, Abdullah D.; Gattan, Hattan; Al-Ahmadi, Bassam M.; Shater, Abdullah F.; Mateos-Hernández, Lourdes; Obregón, Dasiel; Messadi, Lilia; et al. (Frontiers in Microbiology, 2025)
IntroductionThe camel-infesting tick, Hyalomma dromedarii, is a prominent ectoparasite in the Middle East and North Africa (MENA) region, critically impacting camel health and acting as a vector for tick-borne pathogens. Despite prior studies on its microbiota, the effects of geographic origin and sex on microbial community structure and functional stability remain poorly understood.MethodsTo address this, we characterized the bacterial microbiota of H. dromedarii ticks collected from camels in Tunisia (TUN) and Saudi Arabia (SA) using 16S rRNA gene sequencing, microbial network analysis, and metabolic pathway prediction.ResultsOur findings indicate a dominant presence of Francisella endosymbionts in Tunisian ticks, suggesting adaptive roles of H. dromedarii ticks in arid ecosystems. Keystone taxa, particularly Staphylococcus and Corynebacterium, were identified as central to microbial network structure and resilience. Moreover, network robustness analyses demonstrated enhanced ecological stability in the Tunisian tick microbiota under perturbation, indicative of higher resilience to environmental fluctuations compared to Saudi Arabian ticks. Additionally, functional pathway predictions further revealed geographically distinct metabolic profiles between both groups (Tunisia vs. Saudi Arabia and males vs. females), underscoring environmental and biological influences on H. dromedarii microbiota assembly.DiscussionThese results highlight region-specific and sex-specific microbial adaptations in H. dromedarii, with potential implications for pathogen transmission dynamics and vector resilience. Understanding these microbial interactions may contribute to improved strategies for tick control and tick-borne disease prevention.